Gestión administrativa y servicios y su efecto en la demanda de la Empresa “Señor Patacón” año 2021. Estrategias de marketing digital - Reyes Morales, Víctor German (2021)
This research work refers to the study of administrative and service management and its effect on the demand of the company "Señor Patacón", which is a company in charge of preparing fast food based on banana (Hamburger, Basket de patacón and patacón pisao) and in the city of Buena Fe, its facilities are located on Av. Felipe Álvarez and Arcadio Fuentes. This study made it possible to determine the inconveniences in the administrative management of the company "Señor Patacón" and what their effects have been on profitability due to the lack of correct administrative strategies, therefore the delimitation of the investigation was focused on the administrative and service area , whose main objective was to analyze the administrative management and services and their effect on the demand of the company "Señor Patacón" in the city of Buena Fe. YEAR 2021., with the diagnosis of this area, the factors that required greater attention were determined in the administrative process, this investigation arose due to the need to have a digital marketing plan, since making a diffusion of the product that is offered can attract customers through the different social networks and thus position the company in the city of Buena Fe. The methodology used for the development of this research was by collecting information from sources primary schools, through surveys of the inhabitants of the city of Buena Fe, it was determined that 62% expressed that sometimes the promotions carried out by the company are known and also in an interview with the owner of the company Señor Patacón it was identified that they do not carry out any Marketing strategy, with this a Digital Marketing Plan is made where the means where the promotions will be carried out were established so that the population knows the product.